IMPLEMENTASI METODE PROBLEM SOLVING DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM PADA KELAS X AKUNTANSI 2 DI SMK NURUT TAQWA SONGGON - Muttaqin, Ahmad Izza; Fauzi, Anis; Fajar, Muhamad Isfan (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2022)
This study aims to explain the Implementation ofMethods Problem Solving in Islamic Religious Education Learning in Class X Accounting 2 at SMK Nurut Taqwa Songgon Academic Year 2020/2021, explaining the supporting factors and inhibiting factors in the use of themethod ProblemSolving at SMK Nurut Taqwa Songgon. The type of research used in this research is descriptive qualitative. Methods of collecting data using non-participant observation methods, semi-structured interviews, and documentation. The research subjects or respondents in the study were the principal, Islamic religious education teacher, students of class X Accounting 2. The validity of the data was carried out by triangulation. And data analysis includes data collection, data reduction, and data presentation. From the results of this study, it can be concluded that the implementation ofmethods problem solving in learning Islamic religious education at SMK Nurut Taqwa Songgon uses three components in the learning process, namely, planning, implementation, evaluation. In planning, educators have prepared learning tools such as syllabus and lesson plans. For the implementation process, educators have carried out in accordance with the steps of themethod problem solving. And for evaluation, the teacher evaluates by means of a written test or test and the teacher sees the activeness and hard work of the students. Supporting factors are support from students, parents and teachers, adequate media, systematic student mindset, not being creative in learning, and especially with professional teachers. There are quite a lot of time inhibiting factors, requiring regular and careful planning, and the lack of motivation of students to study Islamic religious education. Because most students are only interested in learning general science. And also some students who are busy themselves, because some students are not happy with the way a teacher delivers so that it makes noise in the class and disturbs their friends. Lack of confidence and some are still shy in expressing their opinion.